Analysis of the Effect Economic Growth, Open Unemployment Rate, Education, and PAD on Poverty Rate in Lumajang District - Putih, Indira Tunjung; Primandhana, Wiwin Priana (Journal of Business Management and Economic Development, 2024)
Poverty is a global problem faced by many countries in the world, including Indonesia. In an effort to achieve the Sustainable Development Goals (SDGs), poverty reduction is the main focus. This study aims to determine the effect of economic growth, unemployment rate, education, and local revenue on the poverty rate, and analyse the factors that influence poverty in Lumajang Regency. Multiple linear regression analysis method using Eviews 10 analysis tool was used in this study, with the research period covering 2012-2021. The results show that the Local Own Revenue (PAD) and Education Index have a significant influence on the poverty rate, while economic growth and unemployment rate have no significant influence on poverty. The findings suggest that the influence of unemployment, PAD, education, and economic growth on poverty rates in Indonesia is significant.